ACCOUNTABILITY FOR VILLAGE FUND MANAGEMENT IN ANRIHUA VILLAGE, KINDANG DISTRICT, BULUKUMBA REGENCY - Penne, Andi Mawan; Guntur, Muhamamd; Halim, Didin (Universitas Negeri Makassar, 2025)
This research aims to determine the accountability of village fund management in Anrihua Village, Kindang District, Bulukumba Regency. The type of research used is descriptive qualitative with data collection techniques through observation, interviews and documentation. Data analysis techniques include data condensation, data presentation and withdrawal. The results of this research show that Village Fund Management Accountability is integrated with APBDes accountability including the Planning Stage in the Good Category, the Implementation Stage in the Fair Category, the Administration Stage in the Fair Category, the Reporting Stage in the Poor Category, and the Accountability Stage in the Fair Category